Successful pharmaco-mechanical treatment of a subtotally occluded venous bypass graft in a patient presenting with acute coronary syndrome: a case report and review of the current literature on the role of local thrombolysis - Renker, Matthias; Sossalla, Samuel; Schoefthaler, Christoph; Korosoglou, Grigorios (Frontiers in Cardiovascular Medicine, 2025)
Coronary artery bypass grafting (CABG) is a common and effective treatment for patients with complex coronary artery disease. This case report discusses a 75-year-old male patient who presented with angina and shortness of breath due to thrombus formation in a venous graft 20 years after CABG. Initial diagnostics indicated non-ST-elevation myocardial infarction, leading to immediate intervention. Cardiac catheterization revealed thrombus in the vein graft to the large first diagonal branch, necessitating percutaneous coronary intervention. Despite initial efforts, thrombus aspiration and further catheter advancement were unsuccessful. A combination of balloon angioplasty, stent implantation, and intra-arterial thrombolysis with recombinant tissue plasminogen activator (rt-PA) was employed, resulting in significant thrombus reduction and improved coronary flow. Follow-up coronary CT angiography (CCTA) confirmed complete thrombus resolution and patent graft. The patient was discharged with dual antiplatelet therapy and showed favorable outcomes. This case emphasizes the challenges of managing thrombotic complications in venous bypass grafts and highlights the effectiveness of a multifaceted interventional approach combined with CCTA for non-invasive patient follow-up and assessment of treatment success. Furthermore, a review of the current literature on the role of local thrombolysis for occluded coronary artery bypass grafts is provided.